2022
DOI: 10.1038/s41586-022-05157-3
|View full text |Cite
|
Sign up to set email alerts
|

A microbial supply chain for production of the anti-cancer drug vinblastine

Abstract: Monoterpene indole alkaloids (MIAs) are a diverse family of complex plant secondary metabolites with many medicinal properties, including the essential anti-cancer therapeutics vinblastine and vincristine1. As MIAs are difficult to chemically synthesize, the world’s supply chain for vinblastine relies on low-yielding extraction and purification of the precursors vindoline and catharanthine from the plant Catharanthus roseus, which is then followed by simple in vitro chemical coupling and reduction to form vinb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
190
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(196 citation statements)
references
References 50 publications
4
190
0
2
Order By: Relevance
“…Our genomic analysis showed that despite some similarities (e.g., similar gene content, absence of post-γ whole-genome duplication), V. thouarsii genome displays specific genomic features such as a higher TE content and a bigger size compared with other Apocynaceae . This new Apocynaceae genome thereby paves the way for a better understanding of MIA biosynthesis as well as the identification of new and/or more efficient MIA biosynthetic enzymes that can be used in the developing yeast cell factories producing MIAs ( Guirimand et al 2021 ; Kulagina et al 2021 ; Zhang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our genomic analysis showed that despite some similarities (e.g., similar gene content, absence of post-γ whole-genome duplication), V. thouarsii genome displays specific genomic features such as a higher TE content and a bigger size compared with other Apocynaceae . This new Apocynaceae genome thereby paves the way for a better understanding of MIA biosynthesis as well as the identification of new and/or more efficient MIA biosynthetic enzymes that can be used in the developing yeast cell factories producing MIAs ( Guirimand et al 2021 ; Kulagina et al 2021 ; Zhang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using these approaches, genes of interest could be constructed in a highly effective way; meanwhile, the side pathways could be eliminated to a large extent. The targeted antimicrobial or resistance–reversal agents could be produced in the transgenic microorganisms or plants, which have had great success in the production of artemisinin [ 91 ], as well as other valuable compounds such as vinblastine [ 211 , 212 ], etoposide aglycone [ 213 ], vindoline, and catharanthine [ 212 ]. Lastly, with the continuous discovery of new phytochemicals, deep clarification of pharmacological mechanisms, and comprehensive understanding of specific biosynthesis pathways, plant-derived natural products will become increasingly more useful therapeutic antimicrobial candidates in the future.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…As a crucial part of the heterologous expression system, the efficiency and success rate are mostly determined by the chassis cells . There were some widely used hosts, including Escherichia coli, Saccharomyces cerevisiae, Pseudomonas putida, Aspergillus niger, Myxococcus xanthus, and Bacillus subtilis, developed for heterologous expression of primary or secondary metabolites. Based on the important role in antibiotic production and relatively well-established genetic engineering systems, Streptomyces sp. has some advantages in the expression of Actinomycetes -derived BGCs compared with other bacteria and fungi, such as the abundant primary metabolic pathways, unique post-transcriptional modification system, and antibiotic resistance mechanism. ,, Streptomyces coelicolor A3(2) is a model bacterium for the study of Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%